235_arctos_Russia_haploidised_fasta - Barlow, Axel; Cahill, James A.; Hartmann, Stefanie; Theunert, Christoph; Xenikoudakis, Georgios; Fortes, Gloria G.; Paijmans, Johanna L. A.; Rabeder, Gernot; Frischauf, Christine; Grandal-D'Anglade, Aurora; García-Vázquez, Ana; Murtskhvaladze, Marine; et al. (Dryad Digital Repository, 2018)
Haploidised fasta sequence generated by mapping Illumina short reads to the reference genome assembly of the giant panda, then randomly selecting a single high quality nucleotide from the read stack for each position of the reference genome. See the original publication for full details. The raw sequencing data is also available from the European Nucleotide Archive. Note that this file will contain abundant errors in comparison to a consensus base call from high coverage data.